(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
In recent years, influencer marketing has become one of the most powerful tools for digital brand promotion. However, as brands increasingly rely on influencers, questions about the effectiveness and authenticity of different influencer types—micro and macro—have emerged. This study explores the impact of influencer scale on audience engagement, trust, and conversion rates. Findings from previous research indicate that while macro-influencers offer extensive reach and visibility, micro-influencers tend to build stronger personal connections and higher engagement rates due to their perceived authenticity. The paper highlights the growing importance of authenticity as a determinant of marketing success and suggests that combining both influencer types strategically can yield optimal marketing outcomes.